Breathing Problems An Individualized Program - Vodola, Thomas M.; Ocean Township Board of Education, Oakhurst, NJ. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
As one of the components of the Project ACTIVE (All Children Totally Involved Exercising) Teacher Training Model Kit, the manual is designed to enable the educator to organize, conduct, and evaluate individualized-personalized physical education programs for children (prekindergarten through high school) with breathing problems. An introductory chapter covers definitions and student and teacher behavioral objectives. Chapter II explains procedures for identifying the needs of children who suffer from breathing problems and techniques for gathering preprogram information in terms of vital capacity, cardiorespiratory endurance, and self concept. A systematic procedure for assessing student progress effectively is described in Chapter III. Chapter IV shows the interrelationship between the diagnostic and prescriptive processes. Chapter V focuses on the evaluation of student progress at the end of a specific block of time so that a decision can be made regarding subsequent programing. A final chapter outlines diaphragmatic breathing exercises and cardiorespiratory endurance activities designed to strengthen abdominal musculature and proper breathing technique and lead to more efficient and effective utilization of the heart, lungs, and circulatory system. Among appendixes are a flow chart and activity checklist, vital capacity norms, and a list of supply and equipment needs. (SBH)
Availability: Township of Ocean School District, Dow Avenue, Oakhurst, New Jersey 07755 ($4.00).
Sponsoring Agency: Bureau of Elementary and Secondary Education (DHEW/OE), Washington, DC.
ERIC Note: The document is one of the "Developmental and Adapted Physical Education" series; For related information see, EC 101 553-561; Some parts may reproduce poorly.
Educational level discussed: Elementary Secondary Education.
Educational level discussed: Preschool Education.
May also be available online. Address as at 14/8/18
Keywords: Adapted Physical Education; Diagnostic Teaching; Elementary Secondary Education; Individualized Programs; Preschool Education; Special Health Problems; Student Evaluation; Teaching Guides; Project ACTIVE -- Respiration; Guides, General